EVIDENCE BASED CASE REPORT (EBCR): THE EFFECT OF ACUPRESSURE APPLICATION ON LABOR PAIN IN BIRTHING MOTHERS - Ziyan Ulfiah; Diyan Indrayani; Sri Mulyati (Jurnal Kesehatan Siliwangi, 2025)
Childbirth is a physiological process accompanied by significant pain, which can cause physical and psychological stress in mothers giving birth. The pain experienced by mothers during childbirth not only affects their physical condition, but can also influence their psychological well-being, the progress of labor, and maternal-neonatal outcomes. One non-pharmacological intervention that can be used to reduce labor pain is acupressure, which involves applying pressure to specific points on the body to produce an analgesic effect that reduces pain. The purpose this article to determine the effect of acupressure on reducing labor pain in women in active phase 1 of labor. The search for research articles was conducted using the e-databases PubMed, Science Direct, Cochrane, IMR Press, and Google Scholar based on the inclusion criteria of publication within the last 5 years, free full text, research design using RCT and systematic review, in Indonesian or English, resulting in 3 journals that could be reviewed. This study was a case study. The results showed that pregnant women who received acupressure experienced a reduction in pain as measured by the Numeric Rating Scale (NRS) from 7 to 3, indicating that acupressure was proven to reduce labor pain in pregnant women. It is hoped that health workers will use acupressure to reduce labor pain in pregnant women.